Representing Black Britain: Black and Asian Images on Television - Malik, Sarita (SAGE Publications, Limited, 2001)
'One of the most important books on race, representation and politics to come along in a decade' - Henry Giroux, Penn State University Representing Black Britain offers a critical history of Black and Asian representation on British television from the earliest days of broadcasting to the present day.
Keywords: 1-TV; 2-Approches sociologiques; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Europe (corpus analysé); 4-Europe (lieu de production du savoir); 5-Autrice; 5-Créateur.rice PANDC; Royaume-Uni (corpus analysé); Royaume-Uni (lieu de production du savoir); _Nettoyé